2008
DOI: 10.1007/s10661-008-0540-y
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of heavy metal accumulation ratios of some fish species in Enne Dame Lake (Kütahya/Turkey)

Abstract: The metal accumulation levels for muscle, skin, gill, liver and intestine tissues of some Cyprinidae species (Carassius carassius, Condrostoma nasus, Leuciscus cephalus and Alburnus alburnus) in Enne Dame Lake (Kütahya/Turkey), which is mostly fed by hot spring waters, were investigated. Analyses were performed for copper (Cu), zinc (Zn), manganese (Mn), iron (Fe), cobalt (Co), magnesium (Mg), nickel (Ni), chrome (Cr) and boron (B) using inductively coupled plasma-optic emission spectroscopy (ICP-OES), and cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
65
4
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 36 publications
6
65
4
8
Order By: Relevance
“…Mormede and Davies (2001) suggested that the liver was the target organ, showing the detoxification and accumulation role of the liver. The muscle is generally considered to have a weak accumulating potential (Erdoğrul and Erbilir 2007;Uysal et al 2009;Bervoets and Blust 2003). The liver is the preferred organ for metal accumulation which could also be deduced from the present study.…”
Section: Resultssupporting
confidence: 74%
“…Mormede and Davies (2001) suggested that the liver was the target organ, showing the detoxification and accumulation role of the liver. The muscle is generally considered to have a weak accumulating potential (Erdoğrul and Erbilir 2007;Uysal et al 2009;Bervoets and Blust 2003). The liver is the preferred organ for metal accumulation which could also be deduced from the present study.…”
Section: Resultssupporting
confidence: 74%
“…We observed that catfish had the highest concentrations of Co in gills compared to other species, which is in accordance with the findings of Subotić et al [27]. Co concentrations in Prussian carp muscle samples (0.003 mg·kg -1 ) were lower than in samples from Işikli Dam Lake and Karacaören Dam Lake (2.80 mg μg·g -1 dw) [46], but higher than in samples from Enne Dame Lake (ND -not detected) [10]. Muscle samples from pikeperch (0.004 mg·kg -1 ww) and catfish (0.003 mg·kg -1 ww) had higher concentrations of Co than samples from the Danube (0.001 μg·g -1 dw for both species) [27].…”
Section: Resultssupporting
confidence: 91%
“…The detected concentrations of Ni in pikeperch muscle samples (0.049 mg·kg -1 ww) were lower than in samples from the Caspian Sea (1.77 μg·g -1 ww) [44]. The detected concentrations of Ni in Prussian carp muscle samples (0.038 mg·kg -1 ww) were lower than in samples from Işikli Dam Lake and Karacaören Dam Lake (1.57 μg·g -1 dw) [46], but higher than in samples from Enne Dame Lake (ND -not detected) [10].…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…In this present study, it was observed that gills were the primary target of the metal bioaccumulation. Fish absorbs metals from the external environment primarily through their gills [17]. Comparing metal level present in the gills with the other evaluated tissues (liver, kidney and muscle), it was observed that Lead, Nickel and chromium statistically significant in their level of accumulation in the gill of H. longifilis across the two sample locations and in-between the two seasons of the year, Cadmium, Copper, Nickel were found to be highly accumulated in the gill.…”
Section: Discussionmentioning
confidence: 90%